Application of The TPB Model in Analysising the Consumption Behavior Intentions of Organic Halal Food - Hermin Istiasih; Elis Irmayanti; Tjetjep Yusuf Afandi; Bayu Surindra (CV. AFDIFAL MAJU BERKAH, 2022)
The current research is mostly focused on behavioural intentions using the TPB (Theory of Planned Behaviour) model with an understanding of attitude factors. subjective norms, and perceived behavioural control (PBC). A behavioural intention is on organic halal food from the theory of planned behaviour and e-WOM as additional factors for consumers in Kediri, East Java. This study further explains the role of price as a moderating variable for the behavioural intention of organic halal food. A total of 195 responses from respondents and using confirmatory factor analysis for validation and the results were analyzed using structural equation modelling. Attitudes, subjective norms and e-WOM were found to be significant predictors of behavioural intentions of organic halal food. The findings show that price positively moderates the relationship between attitudes, subjective norms, e-WOM and behavioural intentions of organic halal food. Perceived behavioural control was found to have a weak influence on behavioural intention of organic halal food and there was a non-significant interaction between price moderation with perceived behavioural control and behavioural intention of organic halal food. This research theoretically contributes to the literature by introducing the moderating role of price. The results show that price interactions increase the effect of most of the predictors. This study provides an understanding of the consumer's perspective on consumer intentions to behave in consuming organic halal food which will help stakeholders, such as marketers, retailers, and producers, to achieve marketing strategies for the development of this organic halal food further.